2004
DOI: 10.1023/b:emas.0000029897.90755.e6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Causing Variations of Lead and Cadmium Accumulation of Feral Pigeons (Columba livia)

Abstract: In order to understand the factors causing variation of lead and cadmium accumulation in tissues of feral pigeons in Seoul and Ansan, Korea, we investigated their age, food items (crop and gizzard contents) as well as environmental factors such as soil, atmosphere, and local traffic density. The results indicate that concentrations of Pb and Cd were highly increased in the order of eggs < chicks < adults. In food analysis, supplementary foods (rice, small stones, domestic scraps, cements, hairs, Styrofoam, etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
3
20
3
Order By: Relevance
“…The average recoveries of studied PAHs were from 73 to 98% (NAP was excluded from the results due to very low recovery). The number of pigeon samples collected in each city of this study was comparable with other related studies (Nam et al 2004;Lee 2005, 2006). Nonparametric statistical methods (e.g., MannWhitney U Test) were used in SPSS version 12.0 for statistical evaluation of data as the sex-based sample size was quite small, while in other cases with larger sample size, parametric statistical methods (e.g., T-Test) were applied.…”
Section: Quality Controlsupporting
confidence: 89%
See 2 more Smart Citations
“…The average recoveries of studied PAHs were from 73 to 98% (NAP was excluded from the results due to very low recovery). The number of pigeon samples collected in each city of this study was comparable with other related studies (Nam et al 2004;Lee 2005, 2006). Nonparametric statistical methods (e.g., MannWhitney U Test) were used in SPSS version 12.0 for statistical evaluation of data as the sex-based sample size was quite small, while in other cases with larger sample size, parametric statistical methods (e.g., T-Test) were applied.…”
Section: Quality Controlsupporting
confidence: 89%
“…Unlike lung tissue where respiration of ambient air is thought to be the major source of exposure, exposure for the liver is confounded by multiple potential ingestion sources. Previous studies have reported multiple ingestion exposures for pigeons due to their feeding habits, such as ingestion of domestic scrap, cement, hair and styrofoam sprinkled on the ground, all of which can readily bind PAHs from wet and dry deposition from the surrounding air (Hutton and Goodman 1980;Ohi et al 1981;Harrop et al 1990;Nam et al 2004). For example, the location where pigeons were collected in Beijing (the Modern Plaza) was very close to a subway construction area that produced a large amount of air-borne particles and dusts that potentially were deposited on materials consumed by pigeons, thus creating multiple routes of exposure (Tian et al 2007).…”
Section: Relationship Between Tissue Pah Concentration and Major Expomentioning
confidence: 99%
See 1 more Smart Citation
“…Among possible biomonitoring species, birds have been widely used to assess environmental contamination, and in urban and rural environments, the usefulness of the feral pigeon (C. livia) as a bioindicator of pollution has been assessed over the last decades (Nam et al 2004;Schilderman et al 1997). These metropolitan sedentary birds forage on the ground and present abundant, stable populations, mostly associated with human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Larison et al (2000) showed that older birds accumulated substantial amounts in their kidneys during their lives and developed not only renal damage but also less calcium deposition in bones due to general renal failure. Nam et al (2004b) observed age-dependent Cd accumulation in kidney in Rock Pigeon (Columba livia). However, Hindell et al (1999) reported higher Cd concentrations in the kidneys of juvenile Shy Albatross (Thalassarche cauta) and Wandering Albatross (Diomedea exulans) than in adult birds and suggested that cadmium concentrations are regulated to some degree throughout the bird's life, for example by excretion in feathers.…”
Section: Cadmiummentioning
confidence: 86%